Abdominal imaging. Computation and clinical applications : 5th International Workshop, Held in Conjunction with MICCAI 2013, Nagoya, Japan, September 22, 2013. Proceedings - Warfield, Simon; Vannier, Michael W.; Yoshida, Hiroyuki (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 5th International Workshop CCAA 2013, held in conjunction with MICCAI 2013, in Nagoya, Japan, in September 2013. The book includes 32 papers which were carefully reviewed and selected from 38 submissions. The topics covered are abdominal atlases, shape analysis and morphology in abdominal structures and organs, detection of anatomical and functional landmarks, dynamic, functional, physiologic, and anatomical abdominal imaging, registration methods for abdominal intra- and inter-patient variability, augmented reality techniques for intervention, clinical applications in radio-frequency ablation, open surgery, and minimally invasive surgery.